Epidemiological Assessment of Hepatitis C Virus Seroprevalence Among Screened Populations in Arar City, Northern Saudi Arabia - Alanazi, Abdullah; Abdullah, Erlina (Journal of Cultural Analysis and Social Change, 2025)
The Hepatitis C Virus (HCV) infection remains a significant global public health issue, despite advancements in prevention and treatment, highlighting the need for reliable local epidemiological data to support elimination strategies. This study aimed to assess the seroprevalence of HCV infection among individuals tested in Arar City, Northern Saudi Arabia. A descriptive cross-sectional study employed standard HCV screening records from public healthcare facilities, obtaining serological test results and demographic information from institutional laboratory and hospital information systems. Descriptive statistical analysis was employed to evaluate HCV seroprevalence and characterize the screened population. A total of 384 individuals participated, consisting of 57.0% females and 87.8% Saudi nationals, primarily including young to middle-aged adults. Of the persons checked, 383 (99.7%) tested negative for HCV, while one individual (0.3%) tested positive, indicating a negligible seroprevalence in Arar City. The results indicate the effectiveness of national prevention, screening, and blood safety programs in Saudi Arabia; however, the rise of new cases underscores the need for sustained systematic screening, adherence to stringent laboratory diagnostic standards, and improved local surveillance to support ongoing progress towards HCV elimination.